2021
DOI: 10.2147/amep.s301445
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Knowledge and Attitude Towards Dementia Among Undergraduate University Students in Uganda

Abstract: Background Dementia remains a public health concern and a leading cause of disability and dependency among older people worldwide. However, the knowledge and attitudes towards dementia among university students remain unknown. This study assessed the knowledge and attitude towards dementia among university students in Uganda. Methods An online descriptive, cross-sectional study was undertaken from August to November 2020, among undergraduate students from 11 Ugandan uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
2
7
1
Order By: Relevance
“…Surprisingly, the data analysis showed no significant relationships between gender, year of study, and attitude towards dementia. These results are consistent with the previous research that found the respondents in Malaysian universities had a high attitude towards dementia (18). Indeed, this finding is in line with the work of other studies in this field that have linked positive attitudes about dementia with nursing students (19,21,26,27,29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, the data analysis showed no significant relationships between gender, year of study, and attitude towards dementia. These results are consistent with the previous research that found the respondents in Malaysian universities had a high attitude towards dementia (18). Indeed, this finding is in line with the work of other studies in this field that have linked positive attitudes about dementia with nursing students (19,21,26,27,29).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, through clinical experience and education, students' understanding of the needs, care, and support of a person with dementia can grow and develop (17,31). Undeniably, previous studies reported that undergraduate students have a high level of knowledge about dementia (16,17,18,19,20,21,24,25). In addition, Griffith et al (2020) reported that Malaysian undergraduate students significantly had a positive attitude towards people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…This community-based study was designed to investigate the knowledge, awareness, and attitude of Madinah city residents toward AD, which include basic levels of public knowledge on AD de nition, risk factors, symptoms, and treatments, source of information. In general, the majority of the participants have heard about AD (98.2%) which is higher in comparison to a study done in Uganda by Phillip Musoke et al, 78% of the participants (9). Furthermore, in our study, 95.7% were able to identify one correct manifestation related to AD.…”
Section: Attitude Toward Alzheimer's Diseasecontrasting
confidence: 79%
“…Similarly, in Tanzania, dementia knowledge was low and symptoms are simply accepted as a problem of old age or supernatural causes [6]. There is a signi cantly poor knowledge of dementia among Undergraduate University Students in Uganda [10]. Since this study was conducted in a health facility offering care for the elderly, participants might have heard about dementia and this could explain why the study found a higher level of knowledge compared to studies done in population-based settings in Uganda and elsewhere in Africa.…”
Section: Knowledge Of Dementiamentioning
confidence: 99%
“…A study on the knowledge of dementia in South Africa showed only 10% reported knowing what dementia was [9]. Assessment of knowledge of dementia among undergraduate university students in Uganda reported a signi cantly poor knowledge of the disease [10]. In addition, there is a paucity of information on the knowledge of dementia in the general population.…”
Section: Introductionmentioning
confidence: 99%